Neonatal sudden death caused by a novel heterozygous mutation in SLC25A20 gene: A case report and brief literature review. (February 2022) - Li, Xuebo; Zhao, Feng; Zhao, Zuliang; Zhao, Xiangzhong; Meng, Hao; Zhang, Dianbin; Zhao, Shipeng; Ding, Mingxia
Highlights: CACTD is a life-threatening autosomal recessive fatty acid β-oxidation disorder caused by gene mutation. We describe a rare case with a compound heterozygote with c.199–10 T > G and a novel c.1A > T mutation in SLC25A20 gene. This gene mutation poses a high risk of sudden death. CACTD is often asymptomatic or with only some nonspecific symptoms, which increases the possibility of misdiagnosis and medical disputes due to unexpected sudden death of the patient. Extensive vacuolar degeneration was often observed in the heart and liver at autopsy and histopathological examination. However, gene mutation detection is the gold standard for diagnosis of CACTD. Abstract: Carnitine-acylcarnitine translocase deficiency (CACTD) is a rare and life-threatening autosomal recessive disorder of fatty acid β-oxidation (FAO). Most patients with CACTD develop severe metabolic decompensation which deteriorates progressively and rapidly, causing death in infancy or childhood. As CACTD in some patients is asymptomatic or only with some nonspecific symptoms, the diagnosis is easy to be ignored, resulting in sudden death, which often triggers medical disputes. Herein, we report a case of neonatal sudden death with CACTD. The neonate showed a series of severe metabolic crisis, deteriorated rapidly and eventually died 3 days after delivery. Tandem mass spectrometry (MS-MS) screening of dry blood spots before death showed that the level of long-chain acylcarnitines, especially C12-C18 acylcarnitine, was increased significantly, and therefore a diagnosis of inherited metabolic disease (IMD) was suspected. Autopsy and histopathological results demonstrated that there were diffuse vacuoles in the heart and liver of the deceased. Mutation analysis revealed that the patient was a compound heterozygote with c.199–10 T > G and a novel c.1A > T mutation in the SLC25A20 gene. Pathological changes such as heart failure, arrhythmia and cardiac arrest related to mitochondrial FAO disorders are the direct cause of death, while gene mutation is the underlying cause of death.